Evaluation of banking crisis resolution framework in the West African Monetary Zone - Ngozi Eunice Egbuna; Abdoulaye Barry; Eric Adjapong; George Okorie; Oyebanji Joel Olaoye; Augustine Ujunwa; Rita Ntim Fosu; Omar Sherif; Amadou Diallo; Augustine Sao Ngombu (West African Monetary Institute (WAMI), 2021)
In this study, we benchmarked the crisis resolution frameworks of the Member States of the West African Monetary Zone (WAMZ) with the Financial Stability Board's Key Attributes (KAs) of effective resolution regime for financial institutions, using survey-based methodology. Questionnaires, reflecting the essential criteria of each KA were self-administered by WAMZ Member Central Banks. We generally observed that, banking crisis management provisions in the parent legislations of WAMZ Member States had apparent shortcomings when juxtaposed with the KAs. In particular, norms to govern set-off rights, contractual netting, collateralisation agreements and client assets segregation; establishment of crisis management groups; conduct of regular resolvability assessment and recovery and resolution plans are not adequately captured. In the light of increasing cross-border and pan-African banking activities in the Zone, it would be expedient for Member States to strengthen their legal and regulatory frameworks with these provisions relevant for the resolution of such banks.
Keywords: G01; G21; G28; G33; 330; Crisis Resolution; Key Attributes; WAMZ; banking crisis; essential criteria; questionnaire